Analisis Yuridis Normatif Peran Residivis Dalam Pembentukan Jaringan Kejahatan Baru Di Lembaga Pemasyarakata: Perspektif Penologi Dan Sistem Pemasyarakatan Indonesia - Remonic Elisabeth Sitanggang; Pitria Wulan Dari; Asep Suherman (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Prisons, as institutions tasked with the rehabilitation of prisoners, should serve as places to rehabilitate and assist prisoners in reintegrating into society. However, in practice, interactions between prisoners within prisons can give rise to negative dynamics, one of which involves repeat offenders helping to form new criminal networks for first-time offenders.  This phenomenon highlights a contradiction within Indonesia’s correctional system, where an institution intended to help reform behaviour can instead become a place where criminal activities are learned. This study aims to analyse the role of repeat offenders in the formation of new criminal networks within prisons and to examine its impact on Indonesia’s correctional system from a technological perspective.  This study employs a normative legal methodology using both a legislative and a conceptual approach. The research indicates that the relationship between repeat offenders and new inmates within prisons creates a hierarchical structure that facilitates the dissemination of criminal knowledge, draws members into networks, and reinforces their identity as criminals. This situation is exacerbated by an inadequate prisoner classification system and overcrowding in prisons exceeding their capacity.  This study recommends improving the system of grouping and segregating prisoners based on recidivism rates as a crucial step towards breaking the cycle of criminal behaviour within correctional institutions.